STUDI KASUS PERMASALAHAN DALAM PROSES PEMBELAJARAN KONSEP GENETIKA DI SMA NEGERI 2 SEULIMUM KABUPATEN ACEH BESAR - Rufa Hera (LPPM Universitas Cipta Mandiri, 2017)
Genetics is one of the materials in biology learning that has long been believed many students find the material difficult to understand. The scope of the material is wide, lots of it The use of abstract terms and concepts makes it difficult for students to remember important concepts Genetics material. Various factors can influence the quality of student learning. Those are the factors determine the success of learning in a school. This research aims to look at the problem problems in the process of learning genetic concepts at SMA Negeri 2 Seulimum Aceh Besar district. This case study research was conducted at SMA Negeri 2 Seulimum located on Jl. Krueng Raya-Ateuk Lamteuba, Seulimum, Aceh Besar Regency. Research subjects are Biology teachers and students SMA Negeri 2 Seulimum class XII Science. The method used is an exploratory descriptive method using questionnaires, interviews and observation techniques. Case studies are carried out through field studies with a visit to the school in November 2013. Data analysis was carried out qualitatively and displayed in descriptive form. The research results show that there are several factors The problem in genetics learning is related to the model applied, means The learning used includes: learning media, teaching materials, learning resources and utilization laboratory (Science and Computer Laboratory). The conclusion of this research is the learning process in The concept of genetics at SMA Negeri 2 Seulimum is not yet running optimally. Students don't understand yet well the concept of genetics is based on the learning system that has been carried out.